Dualistic Determinants of COVID-19 Vaccination Intention among University Students in China: From Perceived Personal Benefits to External Reasons of Perceived Social Benefits, Collectivism, and National Pride - Phoenix K. H. Mo (MDPI AG, 2021)
Vaccination is one of the most effective ways of controlling the COVID-19 pandemic. However, vaccine hesitancy is prevalent, and relatively few studies have explored how variables related to personal and external motives have affected the intention to vaccinate. The present study investigated the association between perceived personal benefits, variables reflecting external motives (i.e., perceived social benefits, collectivism, and national pride) and intention to receive COVID-19 vaccination among university students in China. The interaction between perceived personal benefits and the three factors reflecting external motives on intention to receive COVID-19 vaccination was also examined. A total of 6922 university students from five provinces of China completed a cross-sectional survey. Results showed that adjusting for significant background variables, perceived personal benefits, perceived social benefits, collectivism, and national pride were all significant factors of intention to receive COVID-19 vaccination. Results from interaction analyses also showed that the association between perceived personal benefits and COVID-19 vaccination intention was stronger among those with lower levels of national pride. Findings highlighted the important role of self-directed interest and external motives in promoting uptake of COVID-19 vaccination.